In-Volume Laser Direct Writing of Silicon—Challenges and Opportunities - Chambonneau, Maxime; Grojo, David; Tokel, Onur; Ilday, Fatih Omer; Tzortzakis, Stelios; Nolte, Stefan (Laser & Photonics Reviews, 2021)
Laser direct writing is a widely employed technique for 3D, contactless, and fast functionalization of dielectrics. Its success mainly originates from the utilization of ultrashort laser pulses, offering an incomparable degree of control on the produced material modifications. However, challenges remain for devising an equivalent technique in crystalline silicon which is the backbone material of the semiconductor industry. The physical mechanisms inhibiting sufficient energy deposition inside silicon with femtosecond laser pulses are reviewed in this article as well as the strategies established so far for bypassing these limitations. These solutions consisting of employing longer pulses (in the picosecond and nanosecond regime), femtosecond-pulse trains, and surface-seeded bulk modifications have allowed addressing numerous applications.
CRIS-Team Scopus Importer:2023-04-20
Keywords: infrared; laser direct writing; laser–matter interaction; nonlinear propagation; processing; silicon